Front Cover: Lactobacillus Casei Zhang Alleviates Shrimp Tropomyosin‐Induced Food Allergy by Switching Antibody Isotypes through the NF‐κB‐Dependent Immune Tolerance. Issue 10 (20th May 2020) - Fu, Linglin; Xie, Menghua; Wang, Chong; Qian, Yi; Huang, Jianjian; Sun, Zhihong; Zhang, Heping; Wang, Yanbo
Abstract : Mol. Nutr. Food Res . 2020, 64, 1900496 DOI: 10.1002/mnfr.201900496 By using a mouse model, Yanbo Wang and co‐workers demonstrate that probiotic Lactobacillus casei Zhang (LcZ) alleviates shrimp tropomyosin‐induced food allergy via maintaining epithelia stability and immune cell homeostasis, which was mediated by NF‐κB signaling. The study, described in article 1900496, suggests LcZ to be a promising immunomodulator and immunotherapy assistor, especially for food allergy.